2007
DOI: 10.1111/j.1742-1241.2007.01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Solifenacin treatment for overactive bladder in Hispanic patients: patient-reported symptom bother and quality of life outcomes from the VESIcare® Open-Label Trial

Abstract: Although numbers were small, Hispanics receiving solifenacin for OAB reported improvement from baseline in symptom bother and HRQoL, as assessed by three independent PRO measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Tolterodine: 1882. Tolterodine 4 mg ER dailyStable but no continued improvement if used 12 additional weeks except in Physical domainDanilova et al [58]Prospective case series57Trospium 15 mg three times daily16 weeksUnknownSexual dysfunction decreasedN/AChapple et al [56]RCT1. Placebo: 2831.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolterodine: 1882. Tolterodine 4 mg ER dailyStable but no continued improvement if used 12 additional weeks except in Physical domainDanilova et al [58]Prospective case series57Trospium 15 mg three times daily16 weeksUnknownSexual dysfunction decreasedN/AChapple et al [56]RCT1. Placebo: 2831.…”
Section: Reviewmentioning
confidence: 99%
“…Fesoterodine likewise was found to improve subjects’ Personal Relationship scores as compared to controls [55]. Other smaller prospective studies have reported some improvement in sexual health following treatment with solifenacin [56] and trospium [57]. Certain trials also found that anti-muscarinic medication may improve coital incontinence.…”
Section: Reviewmentioning
confidence: 99%